Collaborative construction of the closet (in and out): The affordance of interactivity and gay and lesbian employees' identity work online. (January 2023) - Soini, Aleksi; Eräranta, Kirsi
For LGBQ employees, the disclosure and management of sexual identity in the workplace are likely to cause additional identity work. In this paper, we explore how such identity work is undertaken collectively by gays and lesbians on internet forums. Drawing on the literature on discursive identity work and social media affordances, we conduct a netnographic study of two internet forums, and analyse the ways in which these forums enable gay and lesbian employees' identity work and guide their identity management processes. Overall, our study advances knowledge on sexual identity disclosure and management in three main ways. First, by shifting the focus from the identity disclosure accounts of individual gay and lesbian employees to online peer discussions around the topic, it sheds light on the broader context of identity management beyond the workplace. Second, our findings elucidate particular types of collaborative identity work – consulting, legitimating and questioning identity work – enabled by the affordance of interactivity of internet forums that inform and guide gays and lesbians' identity management practices in organisations. Third, we identify and elaborate on specific discursive identity threats – the 'falsehood', 'incoherence', 'exaggeration' and 'outdatedness' of identity – which gay and lesbian employees are likely to encounter when reflecting on and performing specific identity management strategies, such as concealing or revealing their sexual orientation at work.